Diseño y síntesis de análogos quinoxalínicos con potencial actividad quimioterápica - Fabian, Lucas Emanuel (2015)
Quinoxaline compounds form a family of heterocyclic compounds present in many compounds with demonstrated and varied biological activity. \nIn order to contribute to the design of new compounds with anti-HIV activity and / or anti-Trypanosoma cruzi activity, either through its inhibitory action on the reverse transcriptase of human immunodeficiency virus or its inhibition of cruzipain, essential enzyme for development life cycle of Trypanosoma cruzi in this PhD thesis it has been employed various strategies of aided drug design computer, to design potential inhibitors of the above enzyme systems with quinoxaline structure.\nFrom the results achieved by through virtual screening of reverse transcriptase inhibitors and by the novo design or cruzipain inhibitors, the synthesis of 25 compounds containing a quinoxaline ring were proposed. These compounds were synthesized using some common methodologies for the synthesis of quinoxaline system to which modifications were introduced that allowed optimization of them, such as the use of microwave radiation as an energy source. Thus a linear, simple and efficient synthetic route is provided for obtaining 29 quinoxaline compounds, some of them not described before in the literature.\nInitial studies of the anti-Trypanosoma cruzi activity of the designed and synthesized compounds raise the possibility that subsequent assays demonstrate the activity of them and with this, the utility of the computational methods in the design of new active compounds.\n